Ilioinguinal and Iliohypogastric Nerve Block with Anatomical Landmark and Direct Visualization Technique - Raoofi, Zahra; Karimi, Minoodokht Bavarsad; Parvar, Seyedeh Pegah; Parvar, Seyedeh Paniz (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective(s): The aim of the study was to evaluate the efficacy of ilioinguinal and iliohypogastric nerve block with anatomical landmark and direct visualization technique on postoperative pain relief and use of opioids after lower segment caesarean section. Materials and Methods: In a double blinded randomized clinical trial that conducted in Shahid Akbarabadi hospital of Tehran, 150 pregnant women candidate for elective cesarean section included in the study and randomly allocated into two groups (nerve block with bupivacaine0.25% and control). Procedure of cesarean section was equal in all cases and patients were assigned randomly to receive nerve block with either 20ml of 0.25% bupivacaine (group A-case group) or 20ml of normal saline solution (group B - placebo group) 2 hours after operation. Opioids dose was measured during the postoperative period during 8 hours. Postoperative pain was assessed at 2, 4, 6, 8 hours postoperatively with a visual analog scale (VAS). Data analyzed by SPSS. Results: There was a significant decrease in opioid administration and pain on visual analog scale in group A (nerve block), as compared with Group (placebo). 8 hours after the operation, pain severity in both case and control groups were similar. Total dose of opioid administration was significantly lower in group A (p=0.00). Conclusion: This study shows that ilioinguinal and iliohypogastric nerve block with anatomical landmark and direct visualization technique is good substitution for opioid in postoperative pain control in cesarean section Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 83-86